Analyses of polarisation effects and operando detection of lithium deposition in experimental half- and commercial full-cells. (20th December 2022) - Katzer, Felix; Rüther, Tom; Plank, Christian; Roth, Felix; Danzer, Michael A.
Abstract: Fast-charging of lithium-ion batteries provokes lithium deposition, a severe degradation mechanism of the graphitic anode that causes a rapid performance decay and may lead to safety-critical conditions. In this study, an extensive analysis of the polarisation behaviour during fast-charging is conducted for both graphite half-cells and commercial full-cells. Anomalies in the impedance and potential signals during charging and subsequent relaxation are shown, providing deeper insights into the cell behaviour in case of lithium deposition. The impedance measurement is conducted at characteristic frequencies to enable a physical interpretation. For this purpose, the cells are characterised beforehand by electrochemical impedance spectroscopy and a distribution of relaxation times analysis. For the comprehensive experiments, potential and impedance measurements are run during charging with varying C-rates to analyse the polarisation effects for critical and uncritical cases. A sensitivity analysis of the excitation frequency is conducted for the half-cell results which identifies the migration of lithium ions through the SEI as the most suitable process for the detection of lithium deposition. The same process is tracked in the full-cell experiments showing the same trends and demonstrating the transferability and reliability of the method. The comparison with state-of-the-art retrospective detection methods reveals a high sensitivity. A lumped electrochemical model is introduced which elucidates the observed phenomena and extends the understanding of cell behaviour during critical charging events. Graphical abstract: Highlights: Impedance drop caused by lithium deposition firstly shown on graphite half-cells. Characteristic frequencies of dominant processes identified by EIS & DRT. SEI migration identified as the process most affected by lithium deposition. Lumped electrochemical model provides a mechanistic analysis of impedance effects. Detection method enables automated identification of lithium deposition.